Pengaruh Perbedaan Jenis Kelamin Dan Kontrol Diri Terhadap Keputusan Pembelian Impulsif Produk Parfum - Astari, Laksmitha Widya; Widagda K., I Gusti Ngurah Jaya Agung (E-Jurnal Manajemen, 2014)
Normal 0 false false false IN X-NONE X-NONE Perfume which is one of the lifestyle product has become part of the interface that can support a person’s self-confidence. This causes consumers often feel need to buy an expensive perfumes and irrational judgment to fulfill desire to look perfect and in order to follow current trends. Phenomenon of this irrational purchase encourages impulse buying. The aim of this study was to determine the effect of gender differences and self-control in purchase decision perfume products. Results of this research that gender and self-control significantly influence impulsive buying perfume products. Keywords : gender, self-control, perfume, impulse buying. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}